2020
DOI: 10.1002/adma.202005386
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Properties and Molecular Packing Explain Performance and Processing Procedures of Three D18:NFA Organic Solar Cells

Abstract: Organic solar cells (OSCs) have a bright prospect across applications where light weight, flexibility, low costs, and semi-transparent properties are essential. [1-4] Over the years, tremendous efforts have been devoted to the material design, device engineering, theoretical exploration, and large area manufacture of OSCs. [5-9] With Y6 [10] and its derivatives as acceptors, power conversion efficiencies (PCEs) of over 16% have now

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
138
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(147 citation statements)
references
References 48 publications
(55 reference statements)
9
138
0
Order By: Relevance
“…[6][7][8][9] This viewpoint is later challenged by the facts that the excess vibration energy of CT state dissipates faster than the dissociation of CT state [10] and the free carriers are generated from the thermalized cold CT state regardless of the exciting energy. [11][12][13] With a considerable energy offset between the thermalized CT and CS states of 0.3-0.5 eV in state-of-the-art material systems, [14][15][16][17] how to efficiently dissociate the CT exciton into free carriers has been a key issue to achieve high-efficiency OPV devices.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8][9] This viewpoint is later challenged by the facts that the excess vibration energy of CT state dissipates faster than the dissociation of CT state [10] and the free carriers are generated from the thermalized cold CT state regardless of the exciting energy. [11][12][13] With a considerable energy offset between the thermalized CT and CS states of 0.3-0.5 eV in state-of-the-art material systems, [14][15][16][17] how to efficiently dissociate the CT exciton into free carriers has been a key issue to achieve high-efficiency OPV devices.…”
Section: Introductionmentioning
confidence: 99%
“…Among the numerous candidates, organic solar cell (OSC) has attracted considerable attention of researchers due to its potential of lowcost and large-scale fabrication onto the flexible or stretchable substrate (Thompson and Frechet, 2008;Liang et al, 2010;Li et al, 2012;Hou et al, 2018;Yuan et al, 2019). Owing to the continuous development of organic photoelectric materials in recent years, for the bulk heterojunction (BHJ) OSC device, the power conversion efficiency (PCE) has exceeded 18% (Wang et al, 2020), which paves the way for the future commercialization of OSCs. In addition to the active layer, the charge transporting layer (CTL) also plays a critical role in realizing the high-performance of OSCs (Ma et al, 2010;Yip and Jen, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The final morphology was determined by the thermodynamic molecular interaction and kinetic factors cooperatively during the film-forming process (Gao et al, 2016;Ye et al, 2018b;Gao et al, 2019;. Previous studies have shown that miscibility manipulation of the blending materials could be served as an effective way for performance improvements (Ye et al, 2019;Wang Z. et al, 2020;Yi et al, 2020). Our recent work further demonstrated that the miscibility of PT:NFA systems could be precisely manipulated by molecular structure regulations.…”
Section: Introductionmentioning
confidence: 78%